2011
DOI: 10.1159/000327142
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Epidural Tumors of the Spine – Experience of a Decade from the Kashmir Valley

Abstract: We present our experience after analyzing retrospectively the clinicopathological characteristics, surgical approaches, immediate and long-term postoperative complications and survival outcome of pediatric spinal epidural tumors treated over a period of 10 years from 2000 to 2009 in a tertiary-care hospital. Our study included benign and malignant tumors. The majority of our patients were boys (14:8). The duration of symptoms was longer in benign lesions. Non-Hodgkin’s lymphoma was the commonest malignant tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The mean age of patients who develop osteochondroma in the vertebra is less than 20 years, and it occurs more frequently in males [5,6] - the case we reported was a young boy of 8 years. In our previous series about pediatric epidural spinal tumors, we noticed more involvement of boys than girls [1]. Osteochondromas commonly arise from the tip of the spinous process and project outwards [7]; however, in our case it arose from the inner surface of posterior arch of the atlas and projected inside, causing cord compression.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The mean age of patients who develop osteochondroma in the vertebra is less than 20 years, and it occurs more frequently in males [5,6] - the case we reported was a young boy of 8 years. In our previous series about pediatric epidural spinal tumors, we noticed more involvement of boys than girls [1]. Osteochondromas commonly arise from the tip of the spinous process and project outwards [7]; however, in our case it arose from the inner surface of posterior arch of the atlas and projected inside, causing cord compression.…”
Section: Discussionmentioning
confidence: 67%
“…Pediatric epidural spinal tumors form a distinct entity of tumors of which lymphoma/leukemia figures at the top [1,2]. Between 1.3 and 4.1% of solitary osteochondromas arise in the spine [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have suggested hematogenous spreading or direct extension from the nasal sinuses. [ 3 ] According to the 29 pediatric pituitary tuberculosis cases,[ 1 , 2 , 6 , 8 , 10 , 11 , 14 - 16 , 21 , 27 , 35 , 36 ] the age ranged from 2 years to 17 years old, and the mean age in this category is 11.7 years old, affecting females in 58.6% of cases. Only 10.3% of cases had meningitis tuberculosis as a medical history.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Other alternatives were used in this review, such as using stereotactic brain biopsy and endoscopic transventricular biopsy. [ 7 , 16 ] The histopathological examinations of pituitary tuberculosis reveal epithelioid cells, granulomas with or without caseation necrosis, Langhan’s giant cells, and lymphocytes. The reticulin staining aids in demonstrating the loss of the pituitary’s normal reticulin pattern.…”
Section: Discussionmentioning
confidence: 99%